Job Safety Analysis as a Sustainable Solution for Hazard Identification and Control in the Sugarcane Klentek Frame Fabrication Process at PT. XYZ - Achmad Samudra Dewantara; Sherin Ramadhania; Nia Sastra Permata; Muhammad Suryo Panatagomo Abi Suroso; Eka Rachmadi Endarta Putra (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study applies Job Safety Analysis (JSA) as a qualitative method to manage occupational safety and health (OSH) risks in the production of the Frame Klentek Tebu component at PT. XYZ, an agricultural machinery company. Despite having existing OSH programs, the company continues to face high-frequency incidents of near-misses and Lost Time Injuries, mainly due to heavy machinery use, welding, and painting. The initial analysis suggests that these accidents are caused by procedural lapses and inadequate hazard identification at the task level. The JSA process involved analyzing key tasks Cutting, Fit-Up, Welding, Primer Painting, and Finishing Painting to identify hazards such as falling materials, electric shock and burns during welding, and chemical inhalation during painting. A significant finding was the non-compliance with Personal Protective Equipment (PPE), largely due to operator habits. The research proposed a control hierarchy, prioritizing Elimination (e.g., chamfering sharp edges, replacing forklifts with automated conveyors) and Engineering Controls (e.g., proper grounding systems, installing barriers). This JSA serves as an essential tool for embedding safety into Standard Operating Procedures (SOPs), ensuring business continuity, and creating a safer work environment at PT. XYZ.